Water and sodium intake habits and status of ultra-endurance runners during a multi-stage ultra-marathon conducted in a hot ambient environment: an observational field based study - Costa, Ricardo; Teixeira, Ana; Rama, Luis; Swancott, Abigail JM; Hardy, Lisa D; Lee, Benjamin; Camões-Costa, Vera; Gill, Samantha; Waterman, Jessica P; Freeth, Emily C; Barrett, Edel; Hankey, Joanne; et al. (Nutrition journal, 2013)
Background - Anecdotal evidence suggests ultra-runners may not be consuming sufficient water through foods and fluids to maintenance euhydration, and present sub-optimal sodium intakes, throughout multi-stage ultra-marathon (MSUM) competitions in the heat. Subsequently, the aims were primarily to assess water and sodium intake habits of recreational ultra-runners during a five stage 225 km semi self-sufficient MSUM conducted in a hot ambient environment (Tmax range: 32°C to 40°C); simultaneously to monitor serum sodium concentration, and hydration status using multiple hydration assessment techniques. - - Methods - Total daily, pre-stage, during running, and post-stage water and sodium ingestion of ultra-endurance runners (UER, n = 74) and control (CON, n = 12) through foods and fluids were recorded on Stages 1 to 4 by trained dietetic researchers using dietary recall interview technique, and analysed through dietary analysis software. Body mass (BM), hydration status, and serum sodium concentration were determined pre- and post-Stages 1 to 5. - - Results - Water (overall mean (SD): total daily 7.7 (1.5) L/day, during running 732 (183) ml/h) and sodium (total daily 3.9 (1.3) g/day, during running 270 (151) mg/L) ingestion did not differ between stages in UER (p < 0.001 vs. CON). Exercise-induced BM loss was 2.4 (1.2)% (p < 0.001). Pre- to post-stage BM gains were observed in 26% of UER along competition. Pre- and post-stage plasma osmolality remained within normal clinical reference range (280 to 303 mOsmol/kg) in the majority of UER (p > 0.05 vs. CON pre-stage). Asymptomatic hyponatraemia (<135 mmol/L) was evident pre- and post-stage in n = 8 UER, corresponding to 42% of sampled participants. Pre- and post-stage urine colour, urine osmolality and urine/plasma osmolality ratio increased (p < 0.001) as competition progressed in UER, with no change in CON. Plasma volume and extra-cellular water increased (p < 0.001) 22.8% and 9.2%, respectively, from pre-Stage 1 to 5 in UER, with no change in CON. - - Conclusion - Water intake habits of ultra-runners during MSUM conducted in hot ambient conditions appear to be sufficient to maintain baseline euhydration levels. However, fluid over-consumption behaviours were evident along competition, irrespective of running speed and gender. Normonatraemia was observed in the majority of ultra-runners throughout MSUM, despite sodium ingestion under benchmark recommendations.